2023
DOI: 10.1002/adfm.202213818
|View full text |Cite
|
Sign up to set email alerts
|

Review of Broadband Metamaterial Absorbers: From Principles, Design Strategies, and Tunable Properties to Functional Applications

Abstract: Metamaterial absorbers have been widely studied and continuously concerned owing to their excellent resonance features of ultra-thin thickness, light-weight, and high absorbance. Their applications, however, are typically restricted by the intrinsic dispersion of materials and strong resonant features of patterned arrays (mainly referring to narrow absorption bandwidth). It is, therefore essential to reassert the principles of building broadband metamaterial absorbers (BMAs). Herein, the research progress of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(34 citation statements)
references
References 640 publications
0
34
0
Order By: Relevance
“…Metasurfaces are two-dimensional metamaterials consisting of periodic arrays of subwavelength artificial units that offer the advantages of ultrathin thickness, lightweight, design flexibility, and ease of fabrication. In particular, metasurfaces have the ability to arbitrarily manipulate the electromagnetic wave amplitude, phase, frequency, and polarization state. Examples of metasurfaces include absorbers, antennas, polarization converters, , beam shapers, holographic imaging, and other interesting applications. These conventional metasurfaces are mostly static; in other words, their electrical, magnetic, and magnetoelectric responses are fixed by design, and once manufactured, their functions cannot be tuned to meet the requirements of increasingly complex applications. Hence, tunable metasurfaces provide a versatile platform for the dynamic manipulation of electromagnetic waves. Various developments have been made using lumped elements (e.g., varactors and PIN diodes), actively controlled materials (e.g., graphene, ferroelectric materials, liquid crystals, and phase change materials ), and mechanically tunable metasurfaces. …”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces are two-dimensional metamaterials consisting of periodic arrays of subwavelength artificial units that offer the advantages of ultrathin thickness, lightweight, design flexibility, and ease of fabrication. In particular, metasurfaces have the ability to arbitrarily manipulate the electromagnetic wave amplitude, phase, frequency, and polarization state. Examples of metasurfaces include absorbers, antennas, polarization converters, , beam shapers, holographic imaging, and other interesting applications. These conventional metasurfaces are mostly static; in other words, their electrical, magnetic, and magnetoelectric responses are fixed by design, and once manufactured, their functions cannot be tuned to meet the requirements of increasingly complex applications. Hence, tunable metasurfaces provide a versatile platform for the dynamic manipulation of electromagnetic waves. Various developments have been made using lumped elements (e.g., varactors and PIN diodes), actively controlled materials (e.g., graphene, ferroelectric materials, liquid crystals, and phase change materials ), and mechanically tunable metasurfaces. …”
Section: Introductionmentioning
confidence: 99%
“…To realize broad bandwidth, two perpendicular antisymmetric resonators are used 19 . As multiple frequency‐band increase, structure deformation as a toothed resonator, 20 split ring resonator, 21 perforated square‐patch, 22 and so on the tenability of the absorber can be changed by changing material conductivity 23 . This absorber also lacks tenability, unlike the graphene absorber 24 …”
Section: Introductionmentioning
confidence: 99%
“…19 As multiple frequencyband increase, structure deformation as a toothed resonator, 20 split ring resonator, 21 perforated square-patch, 22 and so on the tenability of the absorber can be changed by changing material conductivity. 23 This absorber also lacks tenability, unlike the graphene absorber. 24 The following is a summary of the research issues that have been identified in the recent observation that demonstrate the advancement of dielectric biosensors/absorbers: (i) decreasing the thickness to make the absorber compatible with nanotechnology; (ii) achieving effective parameters with multiband by selecting perfect narrow-band absorption, suitable for biosensing applications; (iii) having a simple structure so that ease to fabricate; and (iv) to resolve the problem of tunability in the dielectric absorber.…”
mentioning
confidence: 99%
“…[10][11][12] Broadband light absorbers have a wide range of applications in various fields, such as an infrared thermal emitter for photovoltaics, an optical coating for thermal imaging cameras, or as a radiation absorbing material for stealth technologies. [13][14][15][16][17][18] For these applications, there is a need for thinner, higher-performing broadband absorbers in order to increase their functionality and integration as device components. Research into ENZ thin film stacks have shown the ability to achieve perfect, broadband absorption of light in thicknesses less than a few hundred nanometers by stacking multiple layers of transparent conducting oxides with varying carrier densities.…”
Section: Introductionmentioning
confidence: 99%